Thermal Insulation Materials and Their Features Applications - Tilovqobilov Nodirbek Nuriddin o'g'li; Karimov Gofur, (European Journal of Life Safety and Stability (2660-9630), 2023)
Increasing energy efficiency and conserving energy are the current focal points of Russia's energy policy. In this regard, the current market for construction materials offers a vast array of heat-insulating materials of various varieties and manufacturers. Their diversity can sometimes lead the consumer down a dead end. Each material's manufacturer touts the material's benefits in its advertising materials, ignoring the material's other characteristics that render its use insufficiently effective or, in some cases, simply inadmissible under certain conditions. This article describes the fundamental principles of comparing materials, enabling the consumer to select the most suitable option for him based on the most important characteristics. The primary categories of heat-insulating materials are examined. As a result of the market analysis, a methodology has been devised that, presented in the form of a table, optimises the selection of a specific product based on a broad set of criteria.